Enhancing English language proficiency in Ghanaian colleges of education: exploring attitudes, challenges, and pedagogical perspectives from tutors and trainees - Anani, Gifty Edna; Nyamekye, Ernest (Papers in Education and Development, 2024)
This study examines factors inhibiting the quality of English language teaching and learning in Ghanaian colleges of education. Using a cross-sectional descriptive survey design, the study employed a mixed methods research approach, involving questionnaires with 128 teacher trainees from four colleges in the Eastern and Greater Accra zones and telephone interviews with 12 English language tutors. The findings reveal that while some teacher trainees have a positive attitude towards the English language course, they struggle with English concepts due to an overloaded curriculum content, limited instructional time, unfamiliar vocabulary, and ineffective teaching methods. Tutors also highlighted students’ poor foundational knowledge, a shortage of experienced educators, and inadequate professional development opportunities. The study calls for a balanced integration of essentialist and progressivist theories to enhance foundational knowledge, interactive learning, and effective teaching methodologies, contributing to improved English language education in Ghana.